Physico-chemical and antioxidant properties of mesocarp and exocarp from Borassus flabellifer - Mohd Hassan, Rodiah; Bakar, Jamilah; Syed Muhammad, Sharifah Kharidah; Abdul Rahman, Russly (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The physico-chemical and antioxidant activity of the mesocarp and exocarp of Borassus flabellifer were determined to assess the potential of the fruit as a food ingredient. Proximate analysis indicated that both mesocarp and exocarp had a high fibre content of 23.92% and 28.20%, respectively, of which 62.5% and 79.4% were insoluble dietary fibre. The soluble dietary fibre was < 0.50% for both samples. Hemicellulose was the major component in the exocarp followed by cellulose and lignin. Meanwhile for the mesocarp, cellulose was the highest component followed by hemicellulose and lignin. Fructose, galactose, glucose, mannose and sucrose were detected in both samples. Phenol and tannins were present in both mesocarp and exocarp; however, saponin was only detected in the mesocarp. Radical scavenging activity (157.05 mM TE/g) and reducing power (213.05 mM Fe2+) of the exocarp were significantly higher as compared to those of the mesocarp.